ANALYSIS OF Fe, Mn, AND Zn CONCENTRATIONS IN MANGROVE SEDIMENTS ALONG THE SOMBER RIVER IN BALIKPAPAN CITY - Ashar, Andini Aulia Ayuk; Paputungan, Mohammad Sumiran; Hamdhani, Hamdhani; Ritonga, Irwan Ramadhan (Jurnal Perikanan Unram, 2025)
Somber River is one of the rivers with mangrove ecosystem in Balikpapan city. The high human activity in Somber River area may produce waste and heavy metal pollution in mangrove ecosystem, especially in sediment. The purpose of this study is to determine the concentration of Fe, Mn and Zn in mangrove sediments. In addition, the values of pollution indices such as contamination level (TK), pollution load index (IBP) and geoaccumulation index (I-Geo) in sediments are also determined along Somber river, Balikpapan city. The research method used in this study is purposive sampling. Sediment samples were taken from 9 sampling points along Somber river. Sediment samples were deconstructed using acid and analyzed using the Atomic Absorption Spectrophotometer (AAS) Aurora AI 1200 to determine the concentration of Fe, Mn, and Zn based on dry weight in µg/g. Based on the analysis, it was found that the Fe concentration in the sediment ranged from 5403 to 12268 µg/g with an average of 9462 ± 2294 µg/g. In Mn, the concentration value was between 2,25 and 23,2 µg/g with an average of 11,4 ± 7,43 µg/g. Then, the Zn concentration was between 16,6 and 61,3 µg/g, with an average of 43,4 ± 17,4 µg/g. The varying concentrations of Fe, Mn and Zn might be related to several human activities, such as industrial activities, boat docks, settlements, fisheries, ports and metal distribution from the Somber river. The concentrations of Mn and Fe at all research stations were lower than the sediment quality standards, except for Fe. The level of Fe, Mn and Zn contamination in sediments was low (TK<1) and not polluted (IBP<1) and the geoaccumulation index (I-geo) was not polluted to polluted (0<I-geo<1).